1992
DOI: 10.1017/s0022215100120341
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organizer regions (NORs) and myoepitheliomas: a comparison with DNA content and clinical course

Abstract: Nucleolar organizer regions (NOR) were studied in 15 salivary gland myoepitheliomas by an argyrophilic staining technic (AgNOR). The AgNOR data were then compared with flow cytometric DNA content of the neoplasms and also with selected clinicopathologic parameters. We conclude that AgNOR's: (1) do not correlate well with DNA cytometric indices and (2) at best, provide redundant information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Although our patient population is small, our findings show that the number of AgNORs is not a useful prognostic indicator in CMM. Similar lack of correlation between AgNOR values and clinical outcome has been shown recently in other nonmelanocytic tumors (28)(29)(30)(31)(32). Based on our observations ancl those of others, we suggest that Ag-NOR count has little or no significance as a prognostic marker in thick melanomas.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although our patient population is small, our findings show that the number of AgNORs is not a useful prognostic indicator in CMM. Similar lack of correlation between AgNOR values and clinical outcome has been shown recently in other nonmelanocytic tumors (28)(29)(30)(31)(32). Based on our observations ancl those of others, we suggest that Ag-NOR count has little or no significance as a prognostic marker in thick melanomas.…”
Section: Discussionsupporting
confidence: 85%
“…Previous sttidies have shown strong coi relalion between AgNOR scores and proliferation indices (17)(18)(19)(20), mitotic ecmnts (21), Itimor grade (22,23), fiow cytometric DNA content (17,20,24,25), and aggie.s.sive biologic behavior (26,27). Other studies have shown the ccjntraiy (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 91%
“…13 However, Carrillo et al found no correlation between nucleolar organizer regions (an indicator of cell proliferative activity) and clinical outcome in benign and malignant myoepithelioma. 27 According to our results, MMEs that showed high proliferative activity, extensive invasion into the surrounding tissue, perineural permeation, and marked cellular pleomorphism had a poor prognosis. In salivary gland tumors, it has been reported that p53 expression is related to histologic type and prognosis.…”
Section: Discussionmentioning
confidence: 53%
“…Data characterizing cellular DNA content of myoepithelioma have been scarce in the literature. In a study of Carrillo et al, 5 all the grade I myoepitheliomas (encapsulated tumors without cellular atypia) were diploid, with low proliferative activity (less than 4% of cells in S-phase). None of these tumors recurred.…”
mentioning
confidence: 95%